2006
DOI: 10.1152/ajpendo.00083.2005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and endothelial effects of trimetazidine on forearm skeletal muscle in patients with type 2 diabetes and ischemic cardiomyopathy

Abstract: . Metabolic and endothelial effects of trimetazidine on forearm skeletal muscle in patients with type 2 diabetes and ischemic cardiomyopathy. Am J Physiol Endocrinol Metab 290: E54 -E59, 2006. First published September 20, 2005 doi:10.1152/ajpendo.00083.2005The aim of the present study was to evaluate the effect of prolonged inhibition of ␤-oxidation on glucose and lipid muscle forearm metabolism and cGMP and endothelin-1 forearm release in patients with type 2 diabetes mellitus and ischemic cardiomyopathy. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 41 publications
4
44
0
4
Order By: Relevance
“…47 Furthermore, improvement in whole-body insulin sensitivity by trimetazidine is accompanied by a metabolic shift from FFA to glucose oxidation in skeletal muscle during euglycemic hyperinsulinemia in diabetic HF patients. 48 Overall, we postulate that such extracardiac metabolic changes may indirectly improve myocardial glucose metabolism and glycolysis, amplifying the effects mediated by the modest decrease in FFA oxidation observed in the cardiac tissue. Of note, the substrate shift should not be drastic because excess rapid deprivation of FFA is potentially harmful in HF, as shown in our previous study, 8 whereas modest FFA inhibition, together with increased insulin sensitivity, as in the present study, appears more physiological and beneficial.…”
Section: Tuunanen Et Al Trimetazidine In Dilated Cardiomyopathymentioning
confidence: 85%
“…47 Furthermore, improvement in whole-body insulin sensitivity by trimetazidine is accompanied by a metabolic shift from FFA to glucose oxidation in skeletal muscle during euglycemic hyperinsulinemia in diabetic HF patients. 48 Overall, we postulate that such extracardiac metabolic changes may indirectly improve myocardial glucose metabolism and glycolysis, amplifying the effects mediated by the modest decrease in FFA oxidation observed in the cardiac tissue. Of note, the substrate shift should not be drastic because excess rapid deprivation of FFA is potentially harmful in HF, as shown in our previous study, 8 whereas modest FFA inhibition, together with increased insulin sensitivity, as in the present study, appears more physiological and beneficial.…”
Section: Tuunanen Et Al Trimetazidine In Dilated Cardiomyopathymentioning
confidence: 85%
“…The long-term metabolic effects of the partial inhibitor of ␤-oxidation trimetazidine were studied in a drug-naïve human model of moderately obese subjects in whom the still flexible stage of the disease is characterized by an increased FAO, and we performed all measurements during fasting to avoid the confounding suppressive effects of insulin on FA metabolism. One previous study, in which the modulation of FA and glucose metabolism by trimetazidine was simultaneously investigated in humans in an organ different from the myocardium (25) in diabetic patients with cardiomyopathy, showed that forearm lipid and glucose oxidation were reciprocally modulated during the insulin-stimulated state, but no changes occurred during the fasting state despite the higher FA turnover typical of fasting vs. insulin-stimulated conditions. Our present study extends previous findings in several regards, since 1) our human model discounts for the confounding actions of disease and multiple medications; 2) we prolonged the treatment period to 1 mo (vs. 15 days); 3) we adopted imaging techniques for the assessment of regional metabolism, thus targeting skeletal muscle and adipose tissue separately; and 4) by combining plasma tracer kinetics and indirect calorimetry, we estimated endogenous glucose production, hepatic insulin sensitivity, and whole body FA release and oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiomyopathic patients with type 2 diabetes, trimetazidine has been shown to improve systemic glucose metabolism, as reflected by a reduction in fasting glycemia and an increase in forearm and whole body glucose uptake during hyperinsulinemic euglycemia (8). The effects on forearm lipid metabolism were investigated only in the short term (15 days), demonstrating a downregulation in lipid oxidation during insulin stimulation (25). The effects of trimetazidine on adipose tissue metabolism and adipokine secretion have not been investigated despite the dominant role played by this organ in the regulation of systemic FA disposal, and production of a variety of hormones and proinflammatory cytokines affecting insulin action, lipolysis, and oxidative stress (45).…”
mentioning
confidence: 99%
“…These results suggest that trimetazidine is a useful adjunct to the current treatments for the patients with ischemic cardiomyopathy (Bertomeu-Gonzalez et al, 2006). Muscle's metabolic and vascular effects of trimetazidine add new interest in the use of trimetazidine in type 2 diabetic patients with ischemic cardiomyopathy (Monti et al, 2006). It has shown improvement in LV function, symptoms, glucose metabolism and endothelial function in such patients (Bhandari & Subramanian, 2007).…”
Section: Experimental and Clinical Findings On Beneficial Effects Of mentioning
confidence: 99%